Joint Utility of Event- Dependent and Environmental Crime Analysis Techniques for Violent Crime Forecasting - Caplan, Joel M. (2013)
Violent crime incidents occurring in Irvington, New Jersey, in 2007 and 2008 are used to assess the joint analytical capabilities of point pattern analysis, hotspot mapping, near-repeat analysis, and risk terrain modeling. One approach to crime analysis suggests that the best way to predict future crime occurrence is to use past behavior, such as actual incidents or collections of incidents, as indicators of future behavior. An alternative approach is to consider the environment in which crimes occur and identify features of the landscape that would be conducive to crime. Thanks to advances in geographic information system technology and federally funded (free) software applications such as CrimeStat III or the Near Repeat Calculator, these methods have recently been made more accessible to “average” users. This study explores the information products that each method offers for the purposes of place-based violent crime forecasting and resource allocation. Findings help to answer questions about where, when, and why violent crimes occur in a jurisdiction. Ways in which event-dependent and environmental crime analysis techniques can be utilized as complementary instruments in a crime analyst’s tool kit are discussed in detail